Faktor-Faktor yang Mempengaruhi Keberlangsungan UMKM di Kabupaten Banyumas Pada Masa Pandemi Covid 19 - Ade Novianti Azhar; Triani Arofah (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2021)
This study aims to determine the effect of financial literacy, use of e-commerce, product innovation, and readiness to change on the sustainability of MSMEs during the Covid-19 pandemic. The sampling technique used purposive sampling with a sample size of 100 MSME actors in Banyumas Regency. The data analysis technique used in the study was multiple regression analysis. The results of this study indicate that: (1) financial literacy has a significant effect on the sustainability of MSMEs; (2) the use of e-commerce has a significant effect on the sustainability of MSMEs; (3) product innovation has no effect for the sustainability of MSMEs; (4) readiness to change has no effect for the sustainability of MSMEs during the Covid-19 pandemic. The implication of this research is that an understanding of financial literacy will help business actors see their financial condition and assist in making the right decisions, especially during this pandemic, so that it will help business actors maintain their business continuity. The use of e-commerce helps business actors reach a wider market, especially during this pandemic, where shopping is mostly done online, so the use of e-commerce will maintain business stability and maintain business continuity.